Religião em Rousseau: a profissão de fé do vigário saboiano - Castro, Luciana Xavier de (2010)
This dissertation analyzes the conceptions of Jean Jacques Rousseau about religion. It takes as the main reference the text The faith profession of the savoyan vicar which is inserted in the book Emilio or of education. In this work the theism was defined as a natural religion that founded his belief in God having as principle: the natural feelings of the men, the consciousness and reason, and the Christian revelation. In this way, we can conclude that Rousseau was Christian because of the belief that the Bible is truly inspired by God, however, we notice that, for him, the Christian religions foundations are not indispensable to the salvation and the believe in God; for understanding that Supreme being speaks directly to the human heart without the need of mediation proposal by religious institutions. Rousseau still asserts that there is a possibility to know God by other means. Rousseau still asserts that there is a possibility to know God by other means, besides the gospels. Thus it was possible to reach the conclusion that the civil religion, described in the Social Contract, is a propose of a practice religious based on principles of sociability, whose main goal is to bring citizens to love and follow the laws set by the State. However, we notice on this religion traits of the rousseauist theism, and that the theism belief is the base of the citizen religion. As a result of the publication of its religious conceptions, Rousseau was rebuked by valid Christian institutions, in which the main accusation was that he defended an antichristian behavior. This censorship was investigated from the pastoral letter, of the Paris archbishop Christophe de Beaumont and Rousseau s answer letter renowned as Letter to Christophe de Beaumont, in which he claim being Christian, but his beliefs weren t attached to the Church ecclesiastics authority, but were based in his consciousness and reason.